Combining Form and Function in Language Teaching: Teaching Grammar Communicatively - Dony Marzuki (Politeknik Negeri Padang, 2014)
The ongoing debate concerning the best method to apply in language teaching, especially in English as Second Language andForeign Language context has been lasting for about forty years now. The first side of debaters is the supporters of form-focusedlanguage teaching method, and the other side is the supporters of function-focused method. In teaching practice, the form-focused methodviews teaching grammar and all its grammatical rules as an absolute requirement while the function-focused method believes thatacquiring good communicative skill in target language is the ultimate goal in second language learning. Both sides claim that the methodthey use in the teaching practice as the best way to make learners acquire the target language well. Despite the advantages offered by eachmethod, some researchers, however, find out that each method is actually not free from weaknesses. By realizing the weakness of eachmethod, it seems rational for not standing on one method only in the language teaching practice. Perhaps, by combining the two methodsin the teaching practice, language teacher will gain advantages and omit weaknesses owned by each method. A new method can be formedby applying formal instruction in communicative activities.